REORGANIZATION OF THE TAX COURT WITHIN THE STATE ADMINISTRATIVE COURT POST CONSTITUTIONAL COURT DECISION NO 26/PUU-XXI/2023 - Negara, Dharma Setiawan; Husban, Husban; Putra Nainggolan, Samuel Dharma; Lufsiana, Lufsiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
Pursuant to Article 24 paragraph (2) of the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia) it is stated that judicial power is exercised by a Supreme Court and judicial bodies under it within the realm of general courts, religious courts, military courts, state administrative courts and by a Constitutional Court. Based on Article 1 number 8 of Law Number 48 of 2009 Concerning Judicial Power (UU 48/2009) there is a special court that has the authority to examine and hear and decide on certain cases which can only be formed within one of the judicial bodies under the Supreme Court. regulated in laws and regulations. The limitation of judicial institutions as stipulated in Article 24 paragraph (2) of the 1945 Constitution of the Republic of Indonesia does not allow for judicial institutions that are not within the scope of the Supreme Court and/or the Constitutional Court. However, there is a judicial institution, namely the Tax Court as stipulated in Article 2 of Law Number 14 of 2002 concerning the Tax Court (UU 14/2002), which is a judicial body that exercises judicial power for taxpayers seeking justice in tax disputes. Regarding the Tax Court, the guidance is carried out by the Supreme Court and the Ministry of Finance. This makes the tax court not completely independent as a judicial institution in general that carries out a judicial function (there is still interference from the executive branch, namely the ministry of finance), plus that the Supreme Court, in order to be able to fully supervise the tax court both technically and administratively, the tax court should be under the judicial institutions under the Supreme Court. This research is a normative juridical research using statutory and conceptual approaches with the aim of finding an ideal arrangement regarding the institutional structure of the tax court in Indonesia